Characteristics of Body Composition in a Group of Local South Darfur Male Goats 1: Carcass Characteristics (Journal of Veterinary Medicine and Animal Production, 2021)
Two groups of local intact black and intact white male goats were studied for body composition. These goats were born in the University farm and they were individually fed for 60 days in the post weaning period when they were 17.81± 1.36 Kg and 15.95± 0.61 Kg, respectively. The age of the two groups was 165 – 277 days and 540 – 584 days, respectively. The two groups did not show sizeable parameter variations to suggest genetic differences in their performance. The effect of age was significantly favourable for most parameters, especially when expressed as weights, to have bigger values. The carcass and its tissue components were evaluated under the effects of slaughter and hot carcass weights. A further evaluation of these was also conducted under the status of body maturity measured in terms of either slaughter or empty body weight relative to the birth weight of the individual animal. The heavier slaughter and hot carcass weights were associated with more carcass and tissue weights, higher dressing percent; relevant to the empty body weight, higher percent lean and fat and more tissue ratio values except for a lower percent bone, and lean: fat ratio values.Greater body maturity, in either respects, SW or EBW, was associated with heavier half carcass, greater carcass length and higher dressing percent (per empty body weight) values. It also yielded more tissue weights and higher percent values of the total lean and fat but non-significantly lower percent values for bone. There were also greater ratio values for carcass compactness, lean: bone, fat: bone, but lesser ratio values for lean: fat in the greater mature bodies